1978
DOI: 10.1099/0022-1317-40-1-45
|View full text |Cite
|
Sign up to set email alerts
|

Infection of Mouse Liver by Human Adenovirus Type 5

Abstract: SUMMARYCBA mice, inoculated intravenously with large doses of adenovirus type 5, showed raised levels of serum aspartate aminotransferase (SAAT; EC 2.6.1.1) and died within a few days from histologically demonstrable hepatic necrosis. After inoculation of I LDs0, virus was rapidly taken up by the tissues where infectivity then declined greatly. Organ titres then increased about Ioo-fold by 48 h p.i. but, in the liver, which showed intranuclear inclusion bodies, and by electron microscopy, scattered intranuclea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
83
0

Year Published

1984
1984
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(88 citation statements)
references
References 2 publications
5
83
0
Order By: Relevance
“…in the liver, a result in accord with previous studies directly or indirectly noting that HAd5 can indeed replicate its DNA to a limited degree upon infection of the murine liver. [32][33][34][35] In contrast, although each of the other Ad serotype genomes were detected in the murine liver at 6 h.p.i., none showed evidence of significant genomic increases (replication) by 24 h.p.i. In fact, there was a significant decrease in the liver content of HAd3, HAd37 and HAd41 genomes by 24 h.p.i.…”
Section: Alternative Serotype Ads Exhibit Significantly Different Biomentioning
confidence: 93%
“…in the liver, a result in accord with previous studies directly or indirectly noting that HAd5 can indeed replicate its DNA to a limited degree upon infection of the murine liver. [32][33][34][35] In contrast, although each of the other Ad serotype genomes were detected in the murine liver at 6 h.p.i., none showed evidence of significant genomic increases (replication) by 24 h.p.i. In fact, there was a significant decrease in the liver content of HAd3, HAd37 and HAd41 genomes by 24 h.p.i.…”
Section: Alternative Serotype Ads Exhibit Significantly Different Biomentioning
confidence: 93%
“…Transaminase elevation is an indicator of liver injury after systemic administration of adenoviruses, 21 and it has been reported after a high-dose injection of oncolytic adenovirus in clinical trials. 22,23 A dose of 5 Â 10 10 viral particles of AdwtRGD caused up to an 80-fold elevation of both AST and ALT compared with non-treated animals ( Figure 2a).…”
Section: Icovir-7 Replication Is Restricted In Normal Cellsmentioning
confidence: 99%
“…Although mice are not the natural host for human Ads, past investigators have found that wild-type human Ads can efficiently infect and replicate in the liver, causing morbidity in these animals at high doses (11). In this same vein, we have previously shown that fully replication-incompetent [E1-,E2b-,E3-] Ad vectors persist for longer periods of time in vivo (beyond 3 weeks postinfection) and induce less inflammation and toxicity at 72 h postinfection (hpi) than do [E1-E3-] Ad vectors (13,20).…”
Section: Systemic Ad Vector Injection Causes a Massive Intracellular mentioning
confidence: 99%